ANALISIS SEMIOTIKA SIMBOL HEWAN DALAM PERCAKAPAN POLITIK DI TWITER - Aloysius Rangga Aditya Nalendra; Sultan Himawan; Jeffry Latumahina; Bryan Kalbu Adhi (Department of Indonesia Language and Literature Teaching, UIN Syarif Hidayatullah Jakarta, 2020)
Abstract: This research is in the form of descriptive qualitative. This study tries to analyze the language phenoma by using Pierce's semiotic theory. Researchers used many data taken from Twitter social media as data taken from January 2018 to November 2019. Empirical data found on Twitter was processed and analyzed using the thick description method. The study conducted observations on social media and conducted data collection with an experimental system for this neutrality study. The results of this study are the discovery of the fact of the use of animal symbols, namely tadpoles, bat and desert lizards in the interaction of the social media world by netizens. Researchers found the meanings and symbols of the use of these animals only as a mocking tool but also became a symbol of guidance to criticize the animal symbol as not only a stigma but also a means of controlling social criticism.Abstrak: Penelitian ini berbentuk deskriptif kualitatif yang bertujuan untuk menganalisa fenoma bahasa dengan teori semiotic Pierce. Peneliti meggunakan beberapa data yang diambil dari media sosial twitter sebagai data empiris yang diambil dalam kurun waktu Januari 2018 hingga November 2019. Data empiris yang ditemukan dalam twitter tersebut diolah dan dianalisa dengan metode thick description. peneliti melakukan observasi di dalam media sosial dan melakukan pengambilan data dengan sistem acak guna menjaga netralitas penelitian ini. Hasil penelitian ini adalah penemuan fakta empiris penggunaan simbol hewan yakni cebong, kampret dan kadal gurun dalam interkasi dunia sosial media yang dilakukan oleh netizen. Peneliti menemukan kesamaan makna dan tujuan penggunaan symbol ketiga hewan tersebut yakni bukan hanya sebagai alat mengejek tetapi juga menjadi symbol petunjuk untuk mengkritik sehingga symbol hewan tersebut bukan saja menjadi stigma namun juga menjadi alat kontrol kritik sosial.